2015
DOI: 10.1073/pnas.1416000112
|View full text |Cite
|
Sign up to set email alerts
|

Cross-language differences in the brain network subserving intelligible speech

Abstract: How is language processed in the brain by native speakers of different languages? Is there one brain system for all languages or are different languages subserved by different brain systems? The first view emphasizes commonality, whereas the second emphasizes specificity. We investigated the cortical dynamics involved in processing two very diverse languages: a tonal language (Chinese) and a nontonal language (English). We used functional MRI and dynamic causal modeling analysis to compute and compare brain ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
48
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(58 citation statements)
references
References 36 publications
7
48
0
1
Order By: Relevance
“…A one-sample t-test was applied to determine group-level activation for intelligibility effect. This process was similar to previous works [26,29].…”
Section: Analysis Methodssupporting
confidence: 84%
“…A one-sample t-test was applied to determine group-level activation for intelligibility effect. This process was similar to previous works [26,29].…”
Section: Analysis Methodssupporting
confidence: 84%
“…In a DCM analysis, they found that the best model to explain the interactivity of these three sites involved auditory inputs driving posterior STS, with the intelligibility of speech modulating feed-forward connectivity from there to the other two sites. A more recent study has replicated this evidence for feed-forward connectivity between posterior and anterior sections of the STS, for both tonal and non-tonal languages (Ge et al, 2015).…”
mentioning
confidence: 72%
“…In a DCM analysis, they found that the best model to explain the interactivity of these three sites involved auditory inputs driving posterior STS, with the intelligibility of speech modulating feed-forward connectivity from there to the other two sites. A more recent study has replicated this evidence for feed-forward connectivity between posterior and anterior sections of the STS, for both tonal and non-tonal languages (Ge et al, 2015).In sum, the work of the last ten years, with support from emerging techniques including MVPA and DCM, indicates important contributions for both posterior and anterior temporal cortex in speech comprehension. Evidence suggests that distributed, sparse neural codes support perception, and these patterns extend across anterior and posterior temporal cortex and into early auditory regions.…”
mentioning
confidence: 76%
“…In this analysis, four ROIs were selected based on a previous language study [39]. These regions indicated brain activations for speech intelligibility effect (intelligible > unintelligible) in the Chinese group.…”
Section: Methodsmentioning
confidence: 99%
“…Fifteen rs-fMRI data sets in each age group were acquired while children were in a natural sleep state. Intrinsic connectivity analysis was conducted with four language-related regions of interest (ROIs), including the left aSTG, left pSTG, right aSTG and left IFG, which had been shown to be activated in adult Chinese native speakers and chosen as ROIs in dynamic causal modeling [39]. Expecting to detect age-related changes at the network level, here, we firstly explored the development of intrinsic connectivity in the language network based on these selected ROIs.…”
Section: Introductionmentioning
confidence: 99%